On reimagining social democracy - Amit Bhaduri (PSL Quarterly Review, 2021)
This short note introduces the debate on the future of economic policy and reform of capitalism, to be hosted in a new temporary section of the journal. It is essential to debate how to achieve a balance between 'bread' (economic security) and 'liberty' (political freedom), in a dynamic sense, implying that the relative importance between the two logical extremes must vary with the context. In the new section, the Review welcomes contributions and comments on the foreseeable future and the options available for economic policy and for reforms at the global and/or national level.
Keywords: P11; P21; D72; 330; editorial; social democracy; bread and liberty